Pengaruh Variasi Konsentrasi Ekstrak Daun Kelor (Moringa aloifera) terhadap Kematian Larva Aedes aegypti - Restiani Sih Harsanti; Ratna Mustika Yasi (UPT Penerbitan Universitas Jember, 2018)
Dengue Hemorrhagic Fever (DHF) is a disease caused by a virus through the intermediary Aedes aegypti mosquito. This disease spreads throughout the world and endangers and threatens human survival. Efforts to control vectors using synthetic larvicides commonly used are still less effective and inadequate. The purpose of this study was to determine the optimum concentration of Moringa leaf extract for larvicidal activity. Moringa leaf extract was macerated with ethanol, then the extract was carried out by larvacide testing. Variations in concentration in the larvicide test were 1000ppm, 2000 ppm, 3000 ppm, 4000 ppm and 5000 ppm. The results showed that Moringa leaf extract can kill larvae at concentrations of 1000 and 2000 ppm with a 6hour death time. At a concentration of 3000 ppm the extract can kill larvae with a 4-hour death time. At concentrations of 4000 ppm and 5000 ppm it can be killed in two hours of death. Based on the results of the study it can be concluded that at a concentration of 5000 ppm Moringa leaf extract is the best concentration for larvae of Aedes aegypti.